Часовые Вселенной: фантастический роман / Евгений Гуляковский - Гуляковский Евгений Яковлевич (Наши звезды, 1999)
Экземпляры: Ф. 11 (20200319) / Инвентарный номер: 45910 / Цена: 50.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Г 94 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44